Simulation of the influence of Ion-produced NO1@x@ and H0@x@ radicals on the Antarctic Ozone depletion with a one-dimensional model - 王贵勤 (Advances in Atmospheric Sciences, 1990)
<正> A one -dimensional time-dependent photochemical model is used to simulate the influence of ion-produced NOx and HOx radicals on the Antarctic ozone depletion in polar night and polar spring at a latitude of 73 degrees south.Vertical transport and nitrogen-oxygen (NOx). hydrogen-oxygen (HOx) prod. 中国科学引文数据库(CSCD) 1 98 7